University Newspapers, Valuing Science and Combating Misinformation: an investigation into the production process of USP, Unesp and Unicamp Newspapers - Campeao, Lara Luiza Baesteiro [UNESP]; Ito, Liliane de Lucena [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2024)
Communication of research results is essential for the full realization of scientific activity, but it still faces significant challenges, such as disinformation, which causes harm to society. This difficulty arises from the incompatibility between the dynamics of Journalism, which seeks the rapid circulation of information, and Science, which requires time for results to mature. The article proposes that university scientific journalism can help bridge this gap in the popularization of Science and improve the representation of reality. The study analyzes the production process of newspapers from USP, Unesp, and Unicamp, focusing on the Science section and investigating news values, agenda formulation, content hierarchy, reporting techniques, consulted sources, and power interferences.
Keywords: University newspapers; Scientific Dissemination; Disinformation; Appreciation of Science